Hemorheological Alterations and Oxidative Damage in Sickle Cell Anemia - Caprari, Patrizia; Massimi, Sara; Diana, Loretta; Sorrentino, Francesco; Maffei, Laura; Materazzi, Stefano; Risoluti, Roberta (Frontiers in Molecular Biosciences, 2019)
Sickle cell anemia (SCA) is the most common hereditary disorder of hemoglobin (Hb) characterized by a mutation in the β globin gene, which leads to synthesis of HbS a hemoglobin which, under hypoxic conditions, gels and leading to the sickling of the red blood cells (RBC). The dehydration of the RBC increases the concentration of the intracellular Hb with an increase in the internal viscosity and consequently a decrease in the erythrocyte deformability Sickle red blood cells due to their difficulty to flow through the microcirculation cause frequent vaso-occlusive episodes, tissue ischemia and infarctions. Moreover the reduced RBC deformability causes cell fragility leading to hemolysis and recently a key role of hemolysis and oxidative stress in the development of vascular dysfunction has been demonstrated. The aim of this study was to evaluate the hemorheological profiles of patients with SCA in order to point out new indices of vascular impairment and, to characterize the membrane oxidative damage of sickled RBC. Blood viscosities, erythrocyte aggregation, and viscoelastic profiles of SCA patients were determined, and the RBC oxidative damage was investigated by comparing metabolic capability and RBC membrane proteins from SCA patients with and without transfusion dependence. The hemorheological profile of SCA subjects demonstrated high blood viscosity, increased RBC aggregation, and decreased RBC deformability. These impaired flow properties were associated with RBC membrane protein oxidation, with degradation of spectrin and increased membrane-bound globin. The comparison between SCA patients with and without transfusion dependence showed metabolic and structural RBC oxidative damage significantly different.